PENGUNAAN INDEKS BMWP-ASPT DAN PARAMETER FISIKA-KIMIA UNTUK MENENTUKAN STATUS KUALITAS SUNGAI BESAR KOTA BANJARBARU - Aditya Rahman (Universitas Sultan Ageng Tirtayasa, 2017)
ABSTRACT This study aims to determine the quality of water by using water physics-chemical parameters and BMWP-ASPT index in Besar River Banjarbaru City. Determination of water quality was using macroinvertebrate. Organisms found then calculated by BMWP-ASPT scoring, based on the score of tolerance on each of family types. The water quality measurement of Besar River was determined by using physics-chemical parameters, diversity index, dominance, and ASPT BMWP score. The water quality of Besar River Banjarbaru based on physics-chemical factors tends to decrease from the upstream to downstream, the Besar River’s water quality based on the diversity of macroinvertebrates was moderate-severe. And based on the BMWP-ASPT score of the macroinvertebrate, both of sampling 1 and 2 were polluted with the category of medium and severe dirty. In general, the decreasing of water quality of Besar River was due to anthropogenic activities, so that the intolerant macroinvertebrates could not survive in polluted waters while the tolerant ones can adapt well to the polluted aquatic environment.